APPLICATION TECHNIQUE OF COMPUTER GRAPHICS FOR NONSTEADY PROCESSES RESEARCH IN MODERN MATERIAL SCIENCE - Victor N. Pustovoit; Sergey A. Grishin; Maria V. Zaitseva (Advanced Engineering Research, 2011)
The application technique of computer graphics for processing the experimental data in the mode of real time is presented. The data are received in the research practice of modern material science.